2015
DOI: 10.1037/pspp0000029
|View full text |Cite|
|
Sign up to set email alerts
|

Narcissism and the use of personal pronouns revisited.

Abstract: [Correction Notice: An Erratum for this article was reported in Vol 109(3) of Journal of Personality and Social Psychology (see record 2015-37773-002). The authors erroneously reported the overall correlation, first stated in the abstract, between Narcissism and total first-person-singular use as .02 (.017) instead of .01 (.010). The misreporting of the overall correlation between Narcissism and total use of first-person singular does not change the results or interpretation in any way (i.e., the near-zero ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(73 citation statements)
references
References 70 publications
2
70
0
1
Order By: Relevance
“…For example, the prominence of CEO's photographs in companies' annual reports is positively associated with CEO's narcissism levels (Chatterjee & Hambrick, 2007;Sedikides & Campbell, 2017). Also, some studies have reported a positive relation between first-pronoun use and narcissism (Chatterjee & Hambrick, 2007;Fast & Funder, 2010;Raskin & Shaw, 1988; but see Carey et al, 2015). Finally, other studies suggest that narcissists have lower self-control, which implies that they are unlikely to delay gratification, that they focus more on their immediate desires, and that they are impulsive or unconstrained by social norms (Miller et al, 2009;Rose, 2007;Vazire & Funder, 2006).…”
Section: Consumer Choices Self-referencing and State Narcissismmentioning
confidence: 99%
“…For example, the prominence of CEO's photographs in companies' annual reports is positively associated with CEO's narcissism levels (Chatterjee & Hambrick, 2007;Sedikides & Campbell, 2017). Also, some studies have reported a positive relation between first-pronoun use and narcissism (Chatterjee & Hambrick, 2007;Fast & Funder, 2010;Raskin & Shaw, 1988; but see Carey et al, 2015). Finally, other studies suggest that narcissists have lower self-control, which implies that they are unlikely to delay gratification, that they focus more on their immediate desires, and that they are impulsive or unconstrained by social norms (Miller et al, 2009;Rose, 2007;Vazire & Funder, 2006).…”
Section: Consumer Choices Self-referencing and State Narcissismmentioning
confidence: 99%
“…Carey et al (2015), for example, investigate the extent to which narcissism is related to the use of the 1st person singular pronoun I and find no statistically significant correlation between I-talk and narcissism despite the large-scale sample employed. Kuo's (1999) analysis of personal pronouns in thirty-six scientific journal articles shows that the 1st person pronoun was used more frequently than others and that a number of semantic references perform multiple functions.…”
Section: Studies On the Pronouns In Textsmentioning
confidence: 99%
“…we are in search for the self as a part of personality in psychology. It is not surprising because a growing body of research suggests that language can be understood as the linguistic representation of the personality concepts (e.g., Carey et al, 2015;Fitzsimons & Kay, 2004;MA & LIU, 2016;Makarova, 2012;McGregor, 2010;Sučylaitė, 2012;XU, SUI, & AN, 2014). The language makes available for the description of personality features.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the I designates the subjective aspect and the me the objective aspect of the self (Thass-Thienemann, 1973). Similarly, Carey et al (2015) have emphasized use of first-person singular pronoun as subjective (I), objective (me), and possessive (mine). McGregor (2010) highlights use of first-person singular pronoun as I, me, my.…”
Section: Pronounsmentioning
confidence: 99%